The importance of identifying the true catalyst when using Randles-Sevcik equation to calculate turnover frequency. (3rd November 2021) - Abdi, Zahra; Vandichel, Matthias; Sologubenko, Alla S.; Willinger, Marc-Georg; Shen, Jian-Ren; Allakhverdiev, Suleyman I.; Najafpour, Mohammad Mahdi
Abstract: Water splitting will become important to store excess renewable electrical energy into hydrogen. Although the oxygen-evolution reaction (OER) by water oxidation is a critical reaction for water splitting, further investigations are needed to find the details of the OER mechanism for various electrocatalysts. More in particular for homogeneous electrocatalysts, the Randles-Sevcik equation has been extensively applied to determine the turnover frequency (TOF). Herein, using vitamin B12 as a case study, we show that the dynamical deposition/dissolution of the heterogeneous catalyst during OER makes the Randles-Sevcik equation too complicated to be used for calculating the TOF. Indeed, the conventionally applied post-characterization methods do not provide sufficient accuracy to prove the homogeneity of OER mechanisms; thus, using the Randles-Sevcik equation to calculate the TOF is not necessarily correct. Graphical abstract: The importance of the formed heterogeneous catalyst on the calculation of turnover frequency was highlighted. Image 1 Highlights: Vitamin B12 was investigated under oxygen-evolution reaction. Vitamin B12 is the precatalyst rather than the true catalyst for oxygen-evolution reaction. Randles-Sevcik equation could not be used when dynamical deposition/dissolution of the catalyst occurs.